HUMAN SPACEFLIGHT: U.S. NATIONAL LEGISLATIONS AND REGULATIONS AS SPACE SHERPAS PAVING THE PATH - Erices Bravo, Álvaro Andrés (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: in the ‘New Space Age’ of the 21st century, there is a hybridization of space activities in which new objects and subjects of law are created outside the classical UN outer space institutions. This paper exposes this phenomenon through the study of the ‘space sherpas’, i.e., the U.S. national space legislations and regulations that are paving the path to a new stage in commercial human spaceflight activities. In addition, the investigation holds that UNISPACE IV, to be celebrated in 2027, is an excellent opportunity to address this topic, although it was not considered in ‘Action 56’ of the Pact for the Future, released by UNGA79. Research methods: study of specialized bibliography, international and national legislations and regulations, observation methods and analysis of human spaceflight information. Results: participation of the private sector as owner and operator of space missions is essential for the growth of a thriving space industry in the U.S. and all over the world. Without having previously established a boundary between airspace and outer space, successful missions such as Polaris Dawn, led by ‘private astronaut’ Jared Isaacman, who accomplished the first private spacewalk, prove that commercial development of outer space does not depend exclusively on that historic and still unresolved debate. If an international interpretation of these commercial space activities is not built by means of an international instrument, the trend will be for each country to establish its own terms and definitions regarding human spaceflight and having the ‘space sherpas’ as a model. Discussion: what is a ‘private astronaut’? Do they seek ‘the benefit of all mankind’ as established in Article I of the 1967 Outer Space Treaty? Are they ‘envoys of mankind’ as Article V OST says? Is the functionalist approach winning the upper hand over the spatialist standpoint?